2018
DOI: 10.1507/endocrj.ej17-0500
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of astaxanthin on a combination of D-galactose and jet lag-induced aging model in mice

Abstract: Oxidative stress caused free radical and mitochondrial damage plays a critical role in the progression of aging and age-related damage at the cellular and tissue levels. Antioxidant supplementation has received growing attention and the effects of antioxidant on aging are increasingly assessed in both animal and human studies. However, additional and more promising treatments that contribute to the expansion of anti-aging therapies are needed. Astaxanthin, a super antioxidant carotenoid and free radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Studies have found that cumulative oxidative stress and low grade inflammation exist during the normal aging process . Consistent with our pervious study, the mRNA expressions of anti‐oxidant enzyme also decreased in peripheral tissues in the current study (Figure ). Recently, probiotics are found to be effective in reducing oxidative damage, increasing free radical scavenging rate, and modifying anti‐oxidative enzymes activity in human cells .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have found that cumulative oxidative stress and low grade inflammation exist during the normal aging process . Consistent with our pervious study, the mRNA expressions of anti‐oxidant enzyme also decreased in peripheral tissues in the current study (Figure ). Recently, probiotics are found to be effective in reducing oxidative damage, increasing free radical scavenging rate, and modifying anti‐oxidative enzymes activity in human cells .…”
Section: Discussionsupporting
confidence: 92%
“…The cDNA was synthesized using a reverse transcriptase kit (Toyobo, Osaka, Japan) according to the manufacturer's instructions. Real‐time quantitative PCR was performed using SYBR Green Realtime PCR Master Mix (Toyobo, Osaka, Japan) in an Eppendorf MasterCyclerep RealPlex2 System (Wesseling‐Berzdorf, Germany), as described previously . Primer sequences of the target genes are listed in Table S1, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ASX reversed the reduced expression pattern of sirtuin1 and klotho. In this study, ASX supplementation prevented liver weight loss, improved locomotive muscle function, and exerted significant anti-aging properties by reducing oxidative stress and improving the expression of age-related genes [ 90 ].…”
Section: Major Biochemical Pathways Involved In Astaxanthin Pro-lomentioning
confidence: 99%
“…Furthermore, an increase in dietary ASTA supplementation from 0 to 100 mg/kg linearly increased the mRNA expression of CAT (P < 0.05). Similarly, in a previous study, dietary ASTA increased the oxidative damage repair potential of mice and upregulated the mRNA levels of GPX1, SOD1, SOD2, and CAT in the liver and kidney [44]. Therefore, it would be interesting to further study the mechanism of how dietary ASTA affects semen quality in aging roosters by improving the antioxidant defense system.…”
Section: Relationship Between Semen Quality and Antioxidant Enzyme Activitymentioning
confidence: 68%